MALL BUSINESS LENDING AS A GUARANTEE FOR THE DEVELOPMENT OF THE COUNTRY - Ortiqov Ulug‘bek Akrombek o‘g‘li (KONFERENSIYALAR, 2025)
Lending to small businesses and private entrepreneurshipplays an important role in GDP growth and in the development of thecountry's economy.Crediting small business and private business plays mainrole in increasing GDP and developing economy of the country.